The Effect of Chemical Compounds on Pigmentation and Depigmentation of Teeth - V. Tomečková; S. Dolinská (Czech Dental Chamber, 2017)
Introduction, aim: The aim of this review is to describe the composition and biochemical importance of pellicle - organic layer at the teeth surface during effect of external environment, different chemical elements and compounds (in fruit, vegetables, food, drink, tobacco), psychotropic agents, on the enamel colour, structure and the oral cavity health. This paper discusses the possible biochemical mechanisms involved in the binding of different pigments - chromogens to the pellicle of the teeth enamel. Natural and synthetic substances from the diet may have coloring or bleaching effect on the teeth enamel. Methods: A comparison of the various chemicals effects from diet on the teeth pigmentation. Results: Explanation of effect of the natural as well as synthetic pigments on the enamel color. Pigments present in tobacco, coffee, wine, carrot and blueberry juices, as well as the excessive use of some chemical elements such as iron, chlorine can adversely change the enamel colour. The chromogen binds to the pellicle of the teeth disposed on the surface or penetrate deeper into the enamel layers. The natural pigments are mainly carotenoids (orange and yellow), flavonoids (purple), chlorophyll (green) which are components in certain fruits, vegetables and a variety of drinks e.g. juices and others that are prepared of the mentioned sources. On the other hand, some foods containing ascorbic acid (apple, tangerine, orange and others) and bromelain (pineapple) have a whitening effect on the teeth, as the result of increased salivation and organic acids content. Conclusion: Organic and chemical components from the environment, food, coming into contact with tooth enamel pellicle and influence the health and colour of teeth either positively or negatively. Natural dyes - chromogens: flavonoids, carotenoids, chlorophylls present in liquids and foodstuffs, as well as synthetic drugs and various chemical elements can be fixed to the various surfaces of pellicle, but also in the inner layers of the enamel and change the color or teeth. Choosing appropriate foods containing ascorbic acid and bromelain can whiten teeth. Some foods, however, on the one hand whiten teeth but on the other hand, with their increased consumption can cause enamel erosion and irreversible damage of the enamel structure. The citrus fruits have these whitening properties as the result of the high content of organic acids, therefore it is important to consume them balanced way.